Hirarki Komunikasi, Relasi Kuasa dan Inkoherensi Peran Ruang Publik pada Forum Pembangunan “Musrenbangdes” - Neka - Fitriyah; Apriliawati Pratiwi (Program Studi Ilmu Komunikasi FISIP Universitas Sultan Ageng Tirtayasa, 2026)
This study aims to reveal problems of communication hierarchy, and power relations in the implementation of Musrenbangdes which have an impact on the disruption of development program policymaking and loss of public space functions in the forum. A qualitative approach with a case study method, applied in this study, interviews with key informants, and observation are the data collection techniques. The results of the study show that the hierarchy of communication, and power relations have an impact on the rigidity and stagnation of communication, so that dialogue and discourse that are prerequisites for the realization of public space are difficult to realize. Communication patterns and communication practices based on communication hierarchies, and power relations reinforce differences in status, roles, and access among Musrenbangdes participants that weaken the functions of the public sphere, vulnerable to interference by various government interests and is no longer a space where people can freely express.